2015
DOI: 10.1038/cddis.2015.67
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA lincRNA-p21 is the major mediator of UVB-induced and p53-dependent apoptosis in keratinocytes

Abstract: LincRNA-p21 is a long noncoding RNA and a transcriptional target of p53 and HIF-1α. LincRNA-p21 regulates gene expression in cis and trans, mRNA translation, protein stability, the Warburg effect, and p53-dependent apoptosis and cell cycle arrest in doxorubicin-treated mouse embryo fibroblasts. p53 plays a key role in the response of skin keratinocytes to UVB-induced DNA damage by inducing cell cycle arrest and apoptosis. In skin cancer development, UVB-induced mutation of p53 allows keratinocytes upon success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 50 publications
(94 reference statements)
1
87
1
2
Order By: Relevance
“…Besides this initial finding in mouse cells, other studies supported the importance of lincRNA-p21 in regulating p53-mediated response in mouse and human models [38,39]. Notably, it has been reported that lincRNA-p21 maintains its role as mediator of p53 activity also in somatic reprograming of murine cells [40].…”
Section: Lncrnas Regulated By P53mentioning
confidence: 72%
“…Besides this initial finding in mouse cells, other studies supported the importance of lincRNA-p21 in regulating p53-mediated response in mouse and human models [38,39]. Notably, it has been reported that lincRNA-p21 maintains its role as mediator of p53 activity also in somatic reprograming of murine cells [40].…”
Section: Lncrnas Regulated By P53mentioning
confidence: 72%
“…Interestingly, the high number of CPD keratinocytes that persisted in UVB plus heat-treated samples, suggests possible impairment of the DNA damage repair mechanisms. Normally, formation of CPDs induces p53-mediated cell cycle arrest and the activation of nucleotide excision repair (NER) mechanisms (Cheo et al, 1996;Hall et al, 2015).…”
Section: Uvb Plus Heat Dna Damage Repair and Cell Survivalmentioning
confidence: 99%
“…Expression levels of lnc-GKN2-1:1, lnc-CD1D-2:1, and lnc-SGCG-5:4 and ROS content were significantly increased after UVB irradiation [19]. Hall et al [20] reported that lincRNA-p21 was highly inducible by UVB and had a key role in triggering UVB-induced apoptotic death. Here, repeated UVA irradiation changed lncRNA expression in human skin fibroblasts.…”
Section: Discussionmentioning
confidence: 99%